Complications Associated with Uterine Artery Embolisation for Fibroids - Maria Memtsa; Hayden Homer (Hindawi Limited, 2012)
Uterine artery embolisation (UAE) is a relative newcomer to the mainstream treatment modalities available for fibroid-related problems. The efficacy of UAE is indisputable and has been shown to be comparable to hysterectomy in the short term in large-scale trials. Moreover, compared with hysterectomy, UAE is less invasive, carries a superior risk profile, and, importantly, preserves the uterus. UAE therefore offers patients symptom relief whilst at the same time retaining reproductive potential. Notably however, although women can have successful pregnancies following UAE, it is becoming increasingly evident that pregnancies after UAE are more risky especially during the early stages. Long-term outcome data from randomised trials involving UAE have very recently become available and show that whilst high satisfaction rates previously identified during early-stage followup are sustained, one notable drawback is a substantial risk of reintervention. It remains to be seen how this facet of UAE will impact on its future uptake.